Effects of Plant Growth Regulators on Seed Germination Teatment of Nymphaea gigantea ‘Atrans’ Hybrid In Vitro Conditions - Noimai, Yaowamal (Journal of Applied Research on Science and Technology (JARST), 2018)
Nymphaea gigantea ‘Atrans’ hybrid seeds were struggled with the germination by the physiological dormancy. The aim of this research was to explore the effects of plant growth regulators on seed germination in 3 periods during storage for 30, 60 and 90 days. First, the seed viability was done by TZ test according to the International Seed Testing Association (ISTA) regulation. In vitro culture of Nymphaea gigantea ‘Atrans’ hybrid using seeds explant in a sterile condition were studied. The seeds were sterilized with NaOCl, CuCl2 and H2O2, cultured on MS for 2 weeks. Then the sterilized seeds were stimulated cultured by KNO3, TDZ and semi-solid MS medium supplement with BAP and IAA. The experiment was managed in a completely randomized design (CRD) with 3 replications and was conducted at a laboratory for plant tissue culture of the Faculty of Science and Technology, RMUTT between December 2016 and March 2017. The results revealed that the highest seed viability test (70.0 %) from 30 days-stored seeds. The highest which were surface sterilized with 7.5 and 4.0 % H2O2 for 5 minutes per times gave 100% of sterilized seeds from 60 days-stored seeds. The seed germination treatment with appropriate concentration of TDZ were significant different (p≤0.05). The highest seed germination 88.89 % from 30 days-stored seeds by 2 mgl-1 TDZ within 8 weeks and 66.67 % by 0.2 mgl-1 KNO3 within 6 weeks.